The Effect Of Work Training And Work Discipline On Employee Performance At PT. Godongijo Asri Cinangka-Depok - Pebriyanti, Sifa; Ilham, Nurul (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
This study aims to determine the effect of job training and work discipline on employee performance at PT Godongijo Asri. The methodology of this study uses a quantitative method with an associative approach. The population in this study were 70 employees at PT Godongijo Asri in Depok City with a sample of 70 employees using saturated samples. Data collection techniques were by observation, interviews and questionnaires. The data analysis method used simple and multiple linear regression tests, correlation coefficients, determination coefficients, partial t tests and simultaneous F tests. The results of this study indicate that there is an effect of job training and work discipline on employee performance at PT Godongijo Asri, this can be proven from the multiple linear regression equation Y = 21.207 = 0.180X1 = 0.231X2. The correlation value is 0.595 (moderate / strong enough). The coefficient of determination R square value is 0.354. The Fcount value is 18.370 > Ftable 3.13 with a significant level of 0.000